Urgensi Pemeriksaan Substantif Sengketa Merek KasoMax dengan Merek Kaso dalam Rangka Perlindungan Hukum Terhadap Merek - Pritama, Natasha; Rahaditya, R. (UNES Law Review, 2023)
Trademark registration in Indonesia refers to a constitutive system with the first-to-file principle. First to file is a trademark registration process that is only granted to the party who submits the application for the first time. The state is not permitted to grant registration to other parties who have a mark that contains similarities to a previous mark that was registered earlier. Trademark registration must go through substantive examination stages so as not to violate other people's rights, considering that registration is a process of granting rights, not granting permission. The purpose of this article is to determine the compliance opinion of appeal commission trademark law related to a trademark dispute involving Kasomax and Kaso, and also know the DJKI responsibilities in this dispute. The research method used is normative legal research with data analysis techniques based on deductive reasoning, which analyzes the considerations of the Mark Appeal Commission Council in connection with the provisions contained in Law Number 20 of 2016 concerning marks and geographical indications relating to the purchase of the KasoMax with the Kaso and its form of responsibility for the two brand struggles. Based on the research conducted, it can be concluded that the application of substantive examination in brand assessment has not been fully implemented, and the responsibility given is in the form of the cancellation of the KasoMax as a form of implementation of the Commercial Court decision.